2022
DOI: 10.1172/jci.insight.160274
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and DNA methylome analyses reveal underlying mechanisms for the racial disparity in uterine fibroids

Abstract: Uterine fibroids (leiomyomas) affect Black women disproportionately in terms of prevalence, incidence, and severity of symptoms. The causes of this racial disparity are essentially unknown. We hypothesized that myometria of Black women are more susceptible to developing fibroids and examined the transcriptomic and DNA methylation profiles of myometria and fibroids from Black and White women for comparison.Myometrial samples cluster by race in both their transcriptome and DNA methylation profiles, whereas fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 79 publications
(132 reference statements)
1
4
0
Order By: Relevance
“…Our data showed that the comparison of gene expression between Lyo and adjacent Myo is similar to the comparison with non-diseased Myo, although for the upregulated lncRNAs, the magnitude of change was more pronounced for most lncRNAs when comparison was made with non-diseased Myo. This finding, along with the significant differences in expression of several lncRNAs in diseased versus non-diseased Myo, supports the notion that the presence of Lyo in and of itself could potentially affect the expression of lncRNA in the adjacent Myo, as previously suggested [44]. However, due to immense heterogeneity in fibroid tissues and our finding demonstrating a similar pattern of differential expression for most lncRNAs using diseased versus non-diseased Myo, the commonly used practice of comparing gene expression levels in Lyo with adjacent Myo is supported.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data showed that the comparison of gene expression between Lyo and adjacent Myo is similar to the comparison with non-diseased Myo, although for the upregulated lncRNAs, the magnitude of change was more pronounced for most lncRNAs when comparison was made with non-diseased Myo. This finding, along with the significant differences in expression of several lncRNAs in diseased versus non-diseased Myo, supports the notion that the presence of Lyo in and of itself could potentially affect the expression of lncRNA in the adjacent Myo, as previously suggested [44]. However, due to immense heterogeneity in fibroid tissues and our finding demonstrating a similar pattern of differential expression for most lncRNAs using diseased versus non-diseased Myo, the commonly used practice of comparing gene expression levels in Lyo with adjacent Myo is supported.…”
Section: Discussionsupporting
confidence: 89%
“…A strength of this study was that comparisons of lncRNA levels were made both with matched Myo from the diseased uteri and with non-diseased Myo in patients not using hormonal medications prior to surgery. A recent study [44] suggested the use of Myo from non-diseased uteri to compare with Lyo is more advantageous than a comparison made with diseased Myo because of potential effects of leiomyomas on the adjacent Myo. Our data showed that the comparison of gene expression between Lyo and adjacent Myo is similar to the comparison with non-diseased Myo, although for the upregulated lncRNAs, the magnitude of change was more pronounced for most lncRNAs when comparison was made with non-diseased Myo.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, total hysterectomy treatment needs to be combined with bilateral salpingectomy at the same time. This will impact their ovarian function in varying degrees [15]. follicle-stimulating hormone (FSH), luteinising hormone (LH) and estradiol (E2) are all commonly used indicators to evaluate sexual hormones.…”
Section: Discussionmentioning
confidence: 99%
“…These epigenetic changes in myometrial tissues are thus primed to a pro-fibroid phenotype that may readily respond to adverse environmental conditions that contribute to fibroid development. Recent evidence found epigenetic mechanisms may underlie the racial differences in fibroid disparities and primed myometrial stem cells are expanded in Black women [ 48 , 49 ]. Taken together, it is plausible that the disproportionate prevalence of fibroids in underserved communities, including Black women, may arise from epigenetic priming of progenitor myometrial cells and otherwise healthy myometrium to a pro-fibroid state early during development that is amenable to the effects of environmental exposures ( i.e ., psychosocial stressors), that, when accumulating over time, may readily transition to fibroids.…”
Section: Discussionmentioning
confidence: 99%